Competence, Motivation and Employee Performance at Baitul Maal Wa Tamwil: Influence Analysis and Recommendations for Human Resource Development - Gautama, Muhammad ‘Isa; Solikhah, Puji; Baharuddin, Baharuddin (STAI Serdang Lubuk Pakam, 2024)
Human resources are an important element for organizational sustainability, yet organizations often face challenges in maximizing their potential. To support optimal work results, this potential must be optimized through adequate competency development and motivation. This study aims to determine the effect of competence and motivation on employee performance directly at Baitul Maal wat Tamwil (BMT) Tamzis Yogyakarta Area. Respondents in this study were 50 permanent employees of BMT Tamzis Yogyakarta Area, with the variables studied including competence, motivation, and performance. Data collection techniques were carried out using a questionnaire, and data analysis was carried out using the Partial Least Squares (PLS) method. The results showed that competence has a positive and significant effect on employee performance with a Path Coefficient value of 0.359, a standard deviation of 0.119, and a significance level of 0.002 (p<0.050). In addition, motivation also has a positive and significant effect on employee performance with a Path Coefficient value of 0.682, a standard deviation of 0.105, and a significance level of 0.006 (p<0.050). This study recommends organizations to improve competency training programs and strengthen motivation systems to maximize employee potential and support optimal performance.